2019
DOI: 10.1186/s12939-019-0918-1
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequalities in low back pain among older people: the JAGES cross-sectional study

Abstract: BackgroundLow back pain is an important public health issue across the world. However, it is unclear whether socioeconomic status (SES) is associated with low back pain. This study determines an association between SES and low back pain among older people.MethodsWe used cross-sectional data derived from the year 2013 across 30 Japanese municipalities. The survey was conducted between October 2013 to December 2013. Functionally independent community-dwelling older adults aged 65 and above (n = 26,037) were elig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
41
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 50 publications
7
41
0
2
Order By: Relevance
“…We also found that lower occupational classifications, i.e., blue-collared workers, were significantly associated with the prevalence of lower back pain; this finding was also consistent with earlier studies [35,36]. These findings were consistent with our previous study, which was conducted with the older population [22], and which indicated that the association between individual-level SES and lower back pain was propagative.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We also found that lower occupational classifications, i.e., blue-collared workers, were significantly associated with the prevalence of lower back pain; this finding was also consistent with earlier studies [35,36]. These findings were consistent with our previous study, which was conducted with the older population [22], and which indicated that the association between individual-level SES and lower back pain was propagative.…”
Section: Discussionsupporting
confidence: 92%
“…We used several covariates on the basis of previous studies [1,21,22,23,24]: age (continuous), gender, educational attainment (≥13 years, <13 years), and occupation (manager, professional, white-collared, blue-collared, and no occupation [including not engaged in an income-earning job]). The cutoff point of educational attainment was also in accordance with previous studies [23,24].…”
Section: Methodsmentioning
confidence: 99%
“…For individual covariates, sociodemographic data, behavior, and health status were used. Sociodemographic covariates included sex, age (65–69, 70–74, 75–79, 80–84, and ≥85 years old), educational background (<10, 10–12, and ≥13 years), equivalent annual income (<2, 2–3.9, and ≥4 million yen per year), and past occupation (white-collar workers, blue-collar workers, primary industry workers, or never worked before) [30,31]. Primary industry workers in agriculture, forestry, and fisheries were considered separately from other blue-collar workers because those three occupations are known to be strongly associated with musculoskeletal pain [32].…”
Section: Methodsmentioning
confidence: 99%
“…Low back pain (LBP) is the top global cause of disability 1 and the incidence rate varies from 0.024-7.0% 2 . The prevalence of LBP is higher among the population groups with low socioeconomic status 3,4 . Data indicated that middle and low-income countries in Asia, Africa, and the Middle East are becoming the epicenter of LBP related disabilities due to an increased number of aged populations and poor health systems in these regions 5 .…”
Section: Introductionmentioning
confidence: 95%